Prognostic factors and treatment results of preoperative intra-arterial concurrent chemoradiation therapy in locally advanced head and neck cancer - Yuan, Tsu-Zong; Wang, Chang-Yu; Leung, Stephen Wan; Pai, Li-Chu; Chen, Matt Chiung-Yu; Leung, Kam-Wing; Huang, Guang-Chen (Therapeutic Radiology and Oncology, 2018)
Background: To retrospectively evaluate the prognostic factors and treatment outcomes of patients treated with intra-arterial concurrent chemo-radiation therapy (IACCRT). Methods: We retrospectively analyzed patients treated with intra-arterial concurrent chemo-radiation therapy between 2010 and 2016. Intra-arterial catheters were placed in superficial temporal arteries. Two different radiotherapy techniques were used, conventional and simultaneous integrated boost (SIB). The significance of each prognostic factor was estimated using survival analysis. Results: 31 patients were sequentially reviewed with median follow-up time of 11.6 months. There was no renal toxicity. Different radiotherapy techniques, conventional dose fraction versus SIB, did not differ significantly, in terms of locoregional-recurrence-free survival (P=0.057) and overall survival (P=0.069). Better overall survival was found in patients receiving salvage surgery than no surgery (P=0.001) as well as in treatment-naïve patients than recurrent ones (P=0.001). Conclusions: Preoperative concurrent intra-arterial chemoradiation therapy is feasible and effective, has lower toxicity when compare to reports from intravenous chemoradiotherapy. SIB may seemly increase the conversion of inoperable tumor into operable tumor when compare the conventional dose fraction, but this may require further prospective study with more patient accrual. Prognostic factor that significantly improves the overall survival is if the patients receive the salvage surgery.